Formulating halal cosmetics: role of lipids, compliance challenges, and technological innovations - Elgharbawy, Amal A.M.; Samsudin, Nurhusna; Mohd Noor, Najihah; Zamarudin, Zalikha (AIJR Publisher, 2025)
Halal cosmetics are designed to meet Islamic and ethical standards, responding to the demand for products that are pure, safe and environmentally friendly. Lipids play an important role in these formulations, servings as essential components for skin hydration, enhancing the skin barrier, and overall product functionality. These lipids are derived from a variety of sources, including plants, animals and microbes. Ensuring the halal-compliance of these lipids is a critical consideration. This chapter explores the use of halal lipids in cosmetics, focusing on their sources, physicochemical properties, functions and compliance with halal standards. Sources of halal lipids, including plant-based options like olive and palm oils, and challenges in replacing non-halal animal derived components, are thoroughly examined. Innovation in halal lipids use, such as creating structured lipids, emulsification techniques and encapsulation methods, are presented as ways to improve product performance and meet evolving consumer expectations. Advanced extraction, purification and processing techniques are highlighted to enhance lipid quality while adhering to halal requirements. The discussion extends to sustainable practices in sourcing halal lipids and the environmental impact of their production, alongside the regulatory frameworks guiding halal certification. Looking to the future, the chapter calls for more research into microbial-derived halal lipids and the development of advanced methods to verify ingredient compliance. By combining religious, ethical and scientific perspectives, this chapter offers a clear framework for advancing halal cosmetics and providing insights into how the industry can grow sustainably while meeting the diverse needs of consumers.